ANALISIS PENGGUNAAN OBAT-OBATAN DAN BAHAN MEDIS HABIS PAKAI TERHADAP PENINGKATAN JUMLAH PASIEN DI RUMAH SAKIT H.L. MANAMBAI ABDUL KADIR - Apriliandini, Shinta; Rahayu, Sri (Samalewa: Jurnal Riset & Kajian Manajemen, 2025)
The function and efforts of hospitals in providing healthcare services are supported by auxiliary facilities, one of which is the Pharmacy Installation, which is related to the management of medicines. Hospitals are also responsible for ensuring the safety of medication use for patients. Drug damage not only has negative effects on patients but also harms healthcare facilities as it can hinder optimal medication turnover. The purpose of this study is to analyze the quality of drug and medical consumable management and to examine its relationship with the increase in the number of patients at H.L. Manambai Abdul Kadir Hospital in 2025. The research method uses a quantitative approach with an associative research type, and data processing was conducted using the Statistical Program for Social Sciences (SPSS) version 21. The results of the study indicate that the use of medicines and medical consumables simultaneously has an effect on the increase in the number of patients. However, medical consumables alone do not have a significant impact on the increase in patient numbers. The R-square value is 33.4%, which means that 33.4% of the variation in the increase in patient numbers can be explained by the use of medicines and medical consumables. Efficiency, availability, and quality of medicines must be top priorities in healthcare services.